2019
DOI: 10.1186/s40168-018-0608-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of early events and lifestyle on the gut microbiota and metabolic phenotypes in young school-age children

Abstract: BackgroundThe gut microbiota evolves from birth and is in early life influenced by events such as birth mode, type of infant feeding, and maternal and infant antibiotics use. However, we still have a gap in our understanding of gut microbiota development in older children, and to what extent early events and pre-school lifestyle modulate the composition of the gut microbiota, and how this impinges on whole body metabolic regulation in school-age children.ResultsTaking advantage of the KOALA Birth Cohort Study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
134
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(150 citation statements)
references
References 52 publications
13
134
1
2
Order By: Relevance
“…Each person can present a wide variety of microorganisms in the gut depending on several things, like their lifestyle [52][53][54][55]. It is known that the microbiota varies widely during the first year of life, then it stabilizes as a consortium that resembles that of adults [56].…”
Section: Relationship Between Microbiota and Cardiovascular Diseasesmentioning
confidence: 99%
“…Each person can present a wide variety of microorganisms in the gut depending on several things, like their lifestyle [52][53][54][55]. It is known that the microbiota varies widely during the first year of life, then it stabilizes as a consortium that resembles that of adults [56].…”
Section: Relationship Between Microbiota and Cardiovascular Diseasesmentioning
confidence: 99%
“…Birth by cesarean section, no. (%) 113 (31) 24 (28) 89 (32) .57 239 (30) 40 (32) 185 (30) . models (b 5 1.06, P 5 .003 for foods and b 5 0.22, P 5 .002 for metabolites).…”
Section: Meat Intake Correlates With Intestinal Metabolites and Childmentioning
confidence: 99%
“…It has been argued that these effects need to be considered in terms of the developing microbiota (Goyal et al, 2015). In support of this argument, a recent cohort study in Dutch primary school children found that the strength of the relationship between preschool diet and metabolic phenotype was dependent on microbiota composition (Zhong et al, 2019). Childhood malnutrition delays maturation of the microbiome (Smith et al, 2013;Subramanian et al, 2014), and fecal microbiota transplant from Figure 3 The microbiota-gut-brain axis consists of multiple pathways that allow bidirectional communication between the microbiota and the brain.…”
Section: Metabolism and Nutrient Availabilitymentioning
confidence: 99%